Polyurethane water-blocking adhesive for photovoltaic module frame and preparation method of polyurethane water-blocking adhesive
Through the polyurethane water-blocking glue of specific components, the problem of HJT heterojunction system being sensitive to water vapor is solved, and the high water-blocking performance and weather resistance of the photovoltaic module frame is achieved, which simplifies the process and reduces costs.
Patent Information
- Application Number
- CN202411428735.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The HJT heterojunction system is sensitive to water vapor. The existing silicone + butyl rubber scheme has insufficient water barrier performance and complex process, high cost, and the butyl rubber has weak adhesive force, resulting in attenuation of glue layer defects and water barrier effect.
Polyurethane water-blocking glue consisting of component A and component B with a volume ratio of (0.8~1.2): 1. Component A includes modified castor oil polyol, polyester polyol, liquid polybutadiene polyol, Chain extenders, plasticizers, asphalt, fillers and white carbon black, component B includes isocyanates, liquid polybutadiene polyols, plasticizers, asphalt, fillers, white carbon black and antioxidants, and are mutually connected by specific components. It can improve structural adhesion, sealing and water barrier properties.
实现了光伏组件边框的高阻水性能,简化工艺,降低成本,且在耐候性和紫外光辐照老化后仍保持良好的阻水效果。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water-blocking adhesives, and more specifically to a polyurethane water-blocking adhesive for a photovoltaic module frame and a preparation method thereof. Background Art
[0002] At present, in the field of new energy photovoltaics, the traditional TOPCON technology is not sensitive to water vapor, so the widely used frame sealants are mainly silicone systems; but with the technological updates of photovoltaic module factories, the HJT heterojunction system has become a trend to replace the TOPCON system because it has a higher photoelectric conversion efficiency. However, the HJT heterojunction system is very sensitive to water vapor, so more stringent requirements are put forward for the water barrier performance of the frame sealant.
[0003] However, due to the low cross-linking density, the water-blocking performance of the organic silicon system is insufficient and cannot meet the requirements of the HJT heterojunction system. The current market solution is to use butyl rubber for secondary waterproofing, that is, the process includes two steps, first using organic silicon for sealing and bonding, and then applying butyl hot melt adhesive for water blocking. Because butyl rubber has weak bonding strength, it cannot be used alone.
[0004] However, the existing silicone + butyl rubber solution requires two processes, so it is very complicated in terms of technology and has high equipment requirements. It is not the best model in terms of timeliness or economy. In addition, high molecular weight butyl rubber mainly relies on imports and is expensive, so the overall solution cost is high. On the other hand, butyl rubber has a large molecular weight but a low cross-linking density, so it will face serious creep problems. Although the water-blocking effect is very good in the initial state, as time goes by, the high molecular weight butyl rubber will continue to creep inside, resulting in a lot of defects in the rubber layer, and the water-blocking effect will be significantly reduced. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a polyurethane water-blocking adhesive for a photovoltaic module frame and a preparation method thereof. The polyurethane water-blocking adhesive provided by the present invention has good structural adhesion, sealing, water-blocking and weather resistance, and is particularly suitable for water-blocking sealing of photovoltaic module frames.
[0006] The present invention provides a polyurethane water-blocking adhesive for a photovoltaic module frame, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1;
[0007] The A component comprises:
[0008] 5 to 10 parts by weight of modified castor oil polyol;
[0009] 10 to 20 parts by weight of polyester polyol;
[0010] 5 to 20 parts by weight of liquid polybutadiene polyol;
[0011] 1 to 3 parts by weight of chain extender;
[0012] 5 to 15 parts by weight of plasticizer;
[0013] 20 to 40 parts by weight of asphalt;
[0014] 20 to 40 parts by weight of filler;
[0015] 1 to 3 parts by weight of white carbon black;
[0016] 0.2 to 2 parts by weight of tackifier;
[0017] The B component includes:
[0018] 15 to 40 parts by weight of isocyanate;
[0019] 10 to 40 parts by weight of liquid polybutadiene polyol;
[0020] 10 to 20 parts by weight of plasticizer;
[0021] 10 to 30 parts by weight of asphalt;
[0022] 20 to 40 parts by weight of filler;
[0023] 1 to 3 parts by weight of white carbon black;
[0024] 0.2 to 2 parts by weight of antioxidant;
[0025] 0.2 to 2 parts by weight of water absorbent.
[0026] Preferably, the modified castor oil polyol is selected from Itoh Oil URIC AC-009 and / or Itoh Oil URICAC-006;
[0027] The polyester polyol is selected from Oleon RADIA 7285 and / or Oleon RADIA 7287;
[0028] The liquid polybutadiene polyol is selected from Evonik Polyvest HT and / or Cray Valley Poly bdR45V.
[0029] Preferably, the chain extender is selected from 2-ethyl-1,3-hexanediol and / or 2-butyl-2-ethyl-1,3-propanediol.
[0030] Preferably, the plasticizer is selected from Rutgers Ruetasolv DI and / or Rutgers Novares L100;
[0031] The tackifier is selected from BYK BYK-4511 and / or ShinEtsu KR-517.
[0032] Preferably, the bitumen is selected from TOTAL AZALT 160 / 220 and / or Nynas Nybit E190.
[0033] Preferably, the isocyanate is selected from carbodiimide-uretonimine modified 4,4'-diphenylmethane diisocyanate and / or 4,4'-dicyclohexylmethane diisocyanate.
[0034] Preferably, the antioxidant is selected from one or more of BASF Irganox 1010, BASF Irgafos 168, and BASF Irganox B215.
[0035] The present invention also provides a method for preparing the polyurethane water-blocking adhesive for a photovoltaic module frame according to the above technical solution, comprising the following steps:
[0036] a) Heat modified castor oil polyol, polyester polyol, liquid polybutadiene polyol, chain extender, plasticizer, asphalt, filler and white carbon black to 110°C to 130°C, mix and dehydrate under vacuum, then cool to below 50°C, add tackifier and mix under vacuum to obtain component A;
[0037] b) After the isocyanate and liquid polybutadiene polyol are reacted for the first time, the dried filler, white carbon black, the dehydrated and dispersed plasticizer, asphalt, antioxidant and water absorbent are added to carry out a second reaction to obtain component B;
[0038] c) Mixing the above-mentioned component A and component B in a volume ratio of (0.8-1.2):1 to obtain a polyurethane water-blocking adhesive for a photovoltaic module frame;
[0039] There is no order restriction for step a) and step b).
[0040] Preferably, the mixing method of heating to 110°C to 130°C in step a) is stirring, and the stirring speed is 400rpm to 600rpm;
[0041] The vacuum degree of the vacuum dehydration is -0.08MPa~-0.1MPa, and the time is 1.5h~2.5h;
[0042] The vacuum degree of the vacuum mixing is -0.08MPa~-0.1MPa, the rotation speed is 50rpm~150rpm, and the time is 30min~60min.
[0043] Preferably, the temperature of the first reaction in step b) is 70°C to 90°C, the rotation speed is 80rpm to 120rpm, the vacuum degree is -0.08MPa to -0.1MPa, and the time is 1.5h to 2.5h;
[0044] The temperature of the second reaction is 10°C to 40°C, the rotation speed is 180rpm to 220rpm, the vacuum degree is -0.08MPa to -0.1MPa, and the time is 0.5h to 1.5h.
[0045] The invention provides a polyurethane water-blocking adhesive for a photovoltaic module frame, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1; the component A comprises: 5-10 parts by weight of modified castor oil polyol; 10-20 parts by weight of polyester polyol; 5-20 parts by weight of liquid polybutadiene polyol; 1-3 parts by weight of chain extender; 5-15 parts by weight of plasticizer; 20-40 parts by weight of asphalt; 20-40 parts by weight of filler; 10-20 parts by weight of polyester polyol; 10-20 parts by weight of liquid polybutadiene polyol; 10-20 parts by weight of modified castor oil polyol ... 0 parts by weight; 1 to 3 parts by weight of white carbon black; 0.2 to 2 parts by weight of tackifier; the B component includes: 15 to 40 parts by weight of isocyanate; 10 to 40 parts by weight of liquid polybutadiene polyol; 10 to 20 parts by weight of plasticizer; 10 to 30 parts by weight of asphalt; 20 to 40 parts by weight of filler; 1 to 3 parts by weight of white carbon black; 0.2 to 2 parts by weight of antioxidant; 0.2 to 2 parts by weight of water absorbent. Compared with the prior art, the polyurethane water-blocking adhesive for the photovoltaic module frame provided by the present invention adopts specific components with specific contents to achieve better overall interaction, and at the same time has better structural adhesion, sealing, water blocking, and weather resistance, and is particularly suitable for water blocking and sealing of photovoltaic module frames.
[0046] In addition, the preparation method provided by the present invention has simple process, mild conditions, easy control, low requirements on equipment, and has broad application prospects. DETAILED DESCRIPTION
[0047] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The present invention provides a polyurethane water-blocking adhesive for a photovoltaic module frame, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1;
[0049] The A component comprises:
[0050] 5 to 10 parts by weight of modified castor oil polyol;
[0051] 10 to 20 parts by weight of polyester polyol;
[0052] 5 to 20 parts by weight of liquid polybutadiene polyol;
[0053] 1 to 3 parts by weight of chain extender;
[0054] 5 to 15 parts by weight of plasticizer;
[0055] 20 to 40 parts by weight of asphalt;
[0056] 20 to 40 parts by weight of filler;
[0057] 1 to 3 parts by weight of white carbon black;
[0058] 0.2 to 2 parts by weight of tackifier;
[0059] The B component includes:
[0060] 15 to 40 parts by weight of isocyanate;
[0061] 10 to 40 parts by weight of liquid polybutadiene polyol;
[0062] 10 to 20 parts by weight of plasticizer;
[0063] 10 to 30 parts by weight of asphalt;
[0064] 20 to 40 parts by weight of filler;
[0065] 1 to 3 parts by weight of white carbon black;
[0066] 0.2 to 2 parts by weight of antioxidant;
[0067] 0.2 to 2 parts by weight of water absorbent.
[0068] The present invention provides a two-component polyurethane water-blocking adhesive for water-blocking and sealing of photovoltaic module frames, which solves the high water-blocking requirement for frame adhesive under the new photovoltaic heterojunction (HJT) structure; the present invention aims at solving the two problems mentioned in the background technology by only using one type of glue, and by designing a highly water-blocking two-component polyurethane adhesive, it can meet the requirements for structural bonding, sealing, water blocking, weather resistance, etc. at the same time, which can not only greatly simplify the process but also reduce the cost.
[0069] In the present invention, the polyurethane water-blocking adhesive for the photovoltaic module frame is composed of component A and component B in a volume ratio of (0.8-1.2):1, preferably 1:1.
[0070] In the present invention, the A component comprises:
[0071] 5 to 10 parts by weight of modified castor oil polyol;
[0072] 10 to 20 parts by weight of polyester polyol;
[0073] 5 to 20 parts by weight of liquid polybutadiene polyol;
[0074] 1 to 3 parts by weight of chain extender;
[0075] 5 to 15 parts by weight of plasticizer;
[0076] 20 to 40 parts by weight of asphalt;
[0077] 20 to 40 parts by weight of filler;
[0078] 1 to 3 parts by weight of white carbon black;
[0079] 0.2 to 2 parts by weight of tackifier;
[0080] It is preferably prepared from the following raw materials:
[0081] 5 to 6 parts by weight of modified castor oil polyol;
[0082] 14 to 16 parts by weight of polyester polyol;
[0083] 5 to 15 parts by weight of liquid polybutadiene polyol;
[0084] 1 to 3 parts by weight of chain extender;
[0085] 8 to 12 parts by weight of plasticizer;
[0086] 20 to 30 parts by weight of asphalt;
[0087] 25 to 35 parts by weight of filler;
[0088] 1 to 3 parts by weight of white carbon black;
[0089] 0.5 to 1.5 parts by weight of tackifier.
[0090] In the present invention, the modified castor oil polyol is preferably selected from Itoh Oil URIC AC-009 and / or Itoh Oil URIC AC-006, more preferably Itoh Oil URIC AC-009 or Itoh Oil URIC AC-006. The present invention has no particular limitation on the source of the modified castor oil polyol, and commercial products known to those skilled in the art can be used.
[0091] In the present invention, the polyester polyol is preferably selected from Oleon RADIA 7285 and / or Oleon RADIA 7287, more preferably Oleon RADIA 7285 or Oleon RADIA 7287. The present invention has no particular limitation on the source of the polyester polyol, and commercially available products known to those skilled in the art may be used.
[0092] In the present invention, the liquid polybutadiene polyol is preferably selected from Evonik Polyvest HT and / or Cray Valley Poly bd R45V, more preferably Evonik Polyvest HT or Cray Valley Poly bd R45V. The present invention has no particular limitation on the source of the liquid polybutadiene polyol, and commercially available products known to those skilled in the art may be used.
[0093] In the present invention, the chain extender is preferably selected from 2-ethyl-1,3-hexanediol and / or 2-butyl-2-ethyl-1,3-propanediol, more preferably 2-ethyl-1,3-hexanediol or 2-butyl-2-ethyl-1,3-propanediol. The present invention has no particular limitation on the source of the chain extender, and commercially available products known to those skilled in the art can be used.
[0094] In the present invention, the plasticizer is preferably selected from Rutgers Ruetasolv DI and / or Rutgers Novares L100, more preferably Rutgers Ruetasolv DI or Rutgers Novares L100; the tackifier is preferably selected from BYKBYK-4511 and / or ShinEtsu KR-517, more preferably BYK BYK-4511 or ShinEtsu KR-517. The present invention has no particular restrictions on the sources of the plasticizer and tackifier, and commercially available products known to those skilled in the art can be used.
[0095] In the present invention, the asphalt is preferably selected from TOTAL AZALT 160 / 220 and / or Nynas Nybit E190, more preferably TOTAL AZALT 160 / 220 or Nynas Nybit E190. The present invention has no particular limitation on the source of the asphalt, and commercially available products known to those skilled in the art may be used.
[0096] In the present invention, the filler is preferably selected from Omya Omyacarb 2T-JI and / or Omya Omyacarb 5T-JI, more preferably Omya Omyacarb 2T-JI or Omya Omyacarb 5T-JI; the white carbon black is preferably selected from CABOTCAB-O-SIL TS-720 and / or Evonik AEROSIL R202, more preferably CABOT CAB-O-SIL TS-720 or Evonik AEROSIL R202. The present invention has no particular restrictions on the sources of the filler and white carbon black, and commercially available products known to those skilled in the art may be used.
[0097] In the present invention, the B component comprises:
[0098] 15 to 40 parts by weight of isocyanate;
[0099] 10 to 40 parts by weight of liquid polybutadiene polyol;
[0100] 10 to 20 parts by weight of plasticizer;
[0101] 10 to 30 parts by weight of asphalt;
[0102] 20 to 40 parts by weight of filler;
[0103] 1 to 3 parts by weight of white carbon black;
[0104] 0.2 to 2 parts by weight of antioxidant;
[0105] 0.2 to 2 parts by weight of water absorbent;
[0106] It is preferably prepared from the following raw materials:
[0107] 15 to 20 parts by weight of isocyanate;
[0108] 11 to 16 parts by weight of liquid polybutadiene polyol;
[0109] 10 to 12 parts by weight of plasticizer;
[0110] 20 to 30 parts by weight of asphalt;
[0111] 25 to 35 parts by weight of filler;
[0112] 1 to 3 parts by weight of white carbon black;
[0113] 0.5 to 1.5 parts by weight of antioxidant;
[0114] 0.5 to 1.5 parts by weight of water absorbent.
[0115] In the present invention, the liquid polybutadiene polyol, plasticizer, asphalt, filler and white carbon black are the same as those in the above-mentioned component A, and are not described in detail here.
[0116] In the present invention, the isocyanate is preferably selected from carbodiimide-uretonimine modified 4,4'-diphenylmethane diisocyanate and / or 4,4'-dicyclohexylmethane diisocyanate, and more preferably carbodiimide-uretonimine modified 4,4'-diphenylmethane diisocyanate or 4,4'-dicyclohexylmethane diisocyanate. The present invention has no particular restrictions on the source of the isocyanate, and commercially available products known to those skilled in the art can be used.
[0117] In the present invention, the antioxidant is preferably selected from one or more of BASF Irganox 1010, BASF Irgafos 168, and BASF Irganox B215, and more preferably BASF Irganox 1010 or BASF Irgafos 168. The present invention has no particular limitation on the source of the antioxidant, and commercially available products known to those skilled in the art may be used.
[0118] In the present invention, the water absorbent is preferably Borchers TI; any commercially available product known to those skilled in the art may be used.
[0119] In the present invention, the key performance requirements for the water-blocking adhesive used for the photovoltaic module frame are first clarified: strong adhesion to the aluminum frame, good flexibility, good water-blocking performance, and excellent weather resistance, especially resistance to ultraviolet radiation; according to the above requirements, the present invention selects a two-component polyurethane glue for formula design, and for the adhesion of the aluminum frame, the present invention adds modified castor oil polyols to the formula. This type of resin can significantly improve the bonding strength to aluminum metal; for flexibility, since the polyurethane itself has good flexibility, no special optimization is required; for water-blocking, the water vapor permeability of the polyurethane itself is not low, so it is necessary to add a rubber-based polyol with excellent water-blocking performance; for weather resistance, especially ultraviolet radiation, it is necessary to consider the factor that the double bonds in the rubber-based polyol are destroyed by free radicals generated under ultraviolet light, which is solved by adding an external antioxidant and adding a non-reactive component with good weather resistance.
[0120] On this basis, the main formula design idea of the present invention is: using liquid polybutadiene polyol as the main resin in the system to improve the water-blocking performance of the glue itself; relying on polyester polyols and modified castor oil polyols to improve the adhesion of the glue to the metal substrate; relying on asphalt to improve the water-blocking performance of the glue, while improving the resistance of the glue to ultraviolet radiation aging; relying on antioxidants to improve the resistance of the glue to ultraviolet radiation aging; using plasticizers to improve the flexibility of the glue, and improve the compatibility between asphalt and polyurethane resin. Experimental results show that the polyurethane water-blocking glue for the photovoltaic module frame provided by the present invention adopts specific components in specific contents to achieve better overall interaction, and at the same time has better structural adhesion, sealing, water-blocking, and weather resistance, and is particularly suitable for water-blocking sealing of photovoltaic module frames: the water vapor permeability can be as low as 0.85g / m 2 ·24h, the shear strength of the aluminum substrate is greater than 2.5MPa, the hardness of the glue itself is between 40~70 Shore-A, the tensile strength is greater than 3MPa, and the elongation at break is greater than 300%; after 72h of PCT (high pressure cooking aging, 120℃ / 100% RH / 0.2MPa), the elongation at break is still greater than 200%, and 100% cohesive failure is achieved for the substrate; after 1000h of UV irradiation aging, there is no obvious cracking of the adhesive layer, and the water vapor transmission rate is still less than 5g / m 2 ·24h.
[0121] The present invention also provides a method for preparing the polyurethane water-blocking adhesive for a photovoltaic module frame according to the above technical solution, comprising the following steps:
[0122] a) Heat modified castor oil polyol, polyester polyol, liquid polybutadiene polyol, chain extender, plasticizer, asphalt, filler and white carbon black to 110°C to 130°C, mix and dehydrate under vacuum, then cool to below 50°C, add tackifier and mix under vacuum to obtain component A;
[0123] b) After the isocyanate and liquid polybutadiene polyol are reacted for the first time, the dried filler, white carbon black, the dehydrated and dispersed plasticizer, asphalt, antioxidant and water absorbent are added to carry out a second reaction to obtain component B;
[0124] c) Mixing the above-mentioned component A and component B in a volume ratio of (0.8-1.2):1 to obtain a polyurethane water-blocking adhesive for a photovoltaic module frame;
[0125] There is no order restriction for step a) and step b).
[0126] In the present invention, the above-mentioned raw materials are the same as those described in the above-mentioned technical scheme, and are mainly based on liquid polybutadiene polyol as the main resin, which can achieve low water vapor permeability of the glue. At the same time, with the addition of plasticizers and antioxidants, the adhesion and aging resistance of the glue can be further improved; by adding asphalt to the formula, the UV resistance of the glue can be significantly improved, and the water vapor permeability of the glue can be further reduced; the present invention will not be repeated here.
[0127] In the present invention, the heating to 110°C~130°C mixing in step a) is preferably stirring, and the stirring speed is preferably 400rpm~600rpm, more preferably 500rpm; the vacuum degree of the vacuum dehydration is preferably -0.08MPa~-0.1MPa, and the time is preferably 1.5h~2.5h; the vacuum degree of the vacuum mixing is preferably -0.08MPa~-0.1MPa, the rotation speed is preferably 50rpm~150rpm, more preferably 100rpm, and the time is preferably 30min~60min.
[0128] In the present invention, the temperature of the first reaction in step b) is preferably 70°C to 90°C, more preferably 80°C, the rotation speed is preferably 80rpm to 120rpm, more preferably 100rpm, the vacuum degree is preferably -0.08MPa to -0.1MPa, and the time is preferably 1.5h to 2.5h; the temperature of the second reaction is preferably 10°C to 40°C, more preferably 20°C to 30°C, the rotation speed is preferably 180rpm to 220rpm, more preferably 200rpm, the vacuum degree is preferably -0.08MPa to -0.1MPa, and the time is preferably 0.5h to 1.5h.
[0129] In the present invention, the drying process in step b) is preferably specifically as follows:
[0130] The filler and white carbon black are dried and dehydrated in a drying room at 90°C to 110°C for 45h to 50h to obtain dried filler and white carbon black.
[0131] In the present invention, the dehydration and dispersion process in step b) is preferably specifically as follows:
[0132] The asphalt and plasticizer are dehydrated at 110°C~130°C under vacuum to -0.08MPa~-0.1MPa for 1.5h~2.5h to fully disperse the asphalt in the plasticizer to obtain dehydrated and dispersed plasticizer and asphalt.
[0133] In the present invention, before the first reaction of the liquid polybutadiene polyol in step b), preferably the following steps are further included:
[0134] The liquid polybutadiene polyol is dehydrated at 110°C~130°C under vacuum to -0.08MPa~-0.1MPa for 1.5h~2.5h.
[0135] The preparation method provided by the invention has simple process, mild conditions, easy control, low requirements on equipment, and has broad application prospects.
[0136] The invention provides a polyurethane water-blocking adhesive for a photovoltaic module frame, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1; the component A comprises: 5-10 parts by weight of modified castor oil polyol; 10-20 parts by weight of polyester polyol; 5-20 parts by weight of liquid polybutadiene polyol; 1-3 parts by weight of chain extender; 5-15 parts by weight of plasticizer; 20-40 parts by weight of asphalt; 20-40 parts by weight of filler; 10-20 parts by weight of polyester polyol; 10-20 parts by weight of liquid polybutadiene polyol; 10-20 parts by weight of modified castor oil polyol ... 0 parts by weight; 1 to 3 parts by weight of white carbon black; 0.2 to 2 parts by weight of tackifier; the B component includes: 15 to 40 parts by weight of isocyanate; 10 to 40 parts by weight of liquid polybutadiene polyol; 10 to 20 parts by weight of plasticizer; 10 to 30 parts by weight of asphalt; 20 to 40 parts by weight of filler; 1 to 3 parts by weight of white carbon black; 0.2 to 2 parts by weight of antioxidant; 0.2 to 2 parts by weight of water absorbent. Compared with the prior art, the polyurethane water-blocking adhesive for the photovoltaic module frame provided by the present invention adopts specific components with specific contents to achieve better overall interaction, and at the same time has better structural adhesion, sealing, water blocking, and weather resistance, and is particularly suitable for water blocking and sealing of photovoltaic module frames.
[0137] In addition, the preparation method provided by the present invention has simple process, mild conditions, easy control, low requirements on equipment, and has broad application prospects.
[0138] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials involved in the following examples of the present invention are as follows:
[0139] Isocyanate: Wanhua carbodiimide-uretonimine modified 4,4'-diphenylmethane diisocyanate (CDMDI-100L), Wanhua 4,4'-dicyclohexylmethane diisocyanate (H12MDI);
[0140] Modified castor oil polyols: Itoh Oil URIC AC-009, Itoh Oil URIC AC-006;
[0141] Polyester polyols: Oleon RADIA 7285, Oleon RADIA 7287;
[0142] Liquid polybutadiene polyols: Evonik Polyvest HT, Cray Valley Poly bd R45V;
[0143] Chain extenders: 2-ethyl-1,3-hexanediol (EHD), 2-butyl-2-ethyl-1,3-propanediol (BEPD);
[0144] Plasticizer: Rutgers Ruetasolv DI, Rutgers Novares L100;
[0145] Asphalt: TOTAL AZALT 160 / 220, Nynas Nybit E190;
[0146] Filler: Omya Omyacarb 2T-JI, Omya Omyacarb 5T-JI;
[0147] White carbon black: CABOT CAB-O-SIL TS-720, Evonik AEROSIL R202;
[0148] Tackifier: BYK BYK-4511, ShinEtsu KR-517;
[0149] Antioxidants: BASF Irganox 1010, BASF Irgafos 168, BASF Irganox B215;
[0150] Water absorbent: Borchers TI.
[0151] Example 1
[0152] Component A: 5 parts by weight of URIC AC-009 modified castor oil polyol, 15 parts by weight of RADIA 7285 polyester polyol, 15 parts by weight of Polyvest HT liquid polybutadiene polyol, 2 parts by weight of EHD chain extender, 10 parts by weight of Ruetasolv DI plasticizer, 20 parts by weight of AZALT 160 / 220 asphalt, 30 parts by weight of Omyacarb 2T-JI filler, 2 parts by weight of CAB-O-SIL TS-720 white carbon black, and 1 part by weight of BYK-4511 tackifier;
[0153] Component B: 20 parts by weight of CDMDI-100L isocyanate, 16 parts by weight of Polyvest HT liquid polybutadiene polyol, 10 parts by weight of Ruetasolv DI plasticizer, 20 parts by weight of AZALT 160 / 220 asphalt, 30 parts by weight of Omyacarb 2T-JI filler, 2 parts by weight of CAB-O-SIL TS-720 white carbon black, 1 part by weight of Irganox 1010 antioxidant, and 1 part by weight of TI water absorbent.
[0154] Example 2
[0155] Component A: 5 parts by weight of Uric AC-009 modified castor oil polyol, 15 parts by weight of RADIA 7287 polyester polyol, 10 parts by weight of Poly bd R45V liquid polybutadiene polyol, 2 parts by weight of BEPD chain extender, 10 parts by weight of Novares L100 plasticizer, 25 parts by weight of Nybit E190 asphalt, 30 parts by weight of Omyacarb 5T-JI filler, 2 parts by weight of AEROSIL R202 white carbon black, and 1 part by weight of KR-517 tackifier;
[0156] Component B: 18 parts by weight of CDMDI-100L isocyanate, 13 parts by weight of Poly bd R45V liquid polybutadiene polyol, 10 parts by weight of Novares L100 plasticizer, 25 parts by weight of Nybit E190 asphalt, 30 parts by weight of Omyacarb 5T-JI filler, 2 parts by weight of AEROSIL R202 white carbon black, 1 part by weight of Irgafos 168 antioxidant, and 1 part by weight of TI water absorbent.
[0157] Example 3
[0158] Component A: 5 parts by weight of URIC AC-006 modified castor oil polyol, 15 parts by weight of RADIA 7285 polyester polyol, 5 parts by weight of Polyvest HT liquid polybutadiene polyol, 2 parts by weight of EHD chain extender, 10 parts by weight of Ruetasolv DI plasticizer, 30 parts by weight of AZALT 160 / 220 asphalt, 30 parts by weight of Omyacarb 2T-JI filler, 2 parts by weight of CAB-O-SIL TS-720 white carbon black, and 1 part by weight of KR-517 tackifier;
[0159] Component B: 15 parts by weight of H12MDI isocyanate, 11 parts by weight of Polyvest HT liquid polybutadiene polyol, 10 parts by weight of Ruetasolv DI plasticizer, 30 parts by weight of AZALT 160 / 220 asphalt, 30 parts by weight of Omyacarb 2T-JI filler, 2 parts by weight of CAB-O-SIL TS-720 white carbon black, 1 part by weight of Irganox B215 antioxidant, and 1 part by weight of TI water absorbent.
[0160] Comparative Example 1
[0161] Component A: 10 parts by weight of URIC AC-009 modified castor oil polyol, 20 parts by weight of RADIA 7287 polyester polyol, 20 parts by weight of Poly bd R45V liquid polybutadiene polyol, 2 parts by weight of BEPD chain extender, 10 parts by weight of Novares L100 plasticizer, 30 parts by weight of Omyacarb 5T-JI filler, 2 parts by weight of AEROSIL R202 white carbon black, and 1 part by weight of BYK-4511 tackifier;
[0162] Component B: 30 parts by weight of CDMDI-100L isocyanate, 21 parts by weight of Poly bd R45V liquid polybutadiene polyol, 10 parts by weight of Novares L100 plasticizer, 35 parts by weight of Omyacarb 5T-JI filler, 2 parts by weight of AEROSIL R202 white carbon black, 1 part by weight of Irganox 1010 antioxidant, and 1 part by weight of TI water absorbent.
[0163] The above formula is shown in Table 1 below.
[0164] Table 1
[0165]
[0166] The specific preparation methods of the two-component polyurethane water-blocking adhesive provided in the above embodiments and comparative examples are as follows:
[0167] Component A:
[0168] Modified castor oil polyol, polyester polyol, liquid polybutadiene polyol, chain extender, plasticizer, asphalt, filler and white carbon black were heated to 120°C with stirring at 500 rpm, evacuated to -0.09 MPa and dehydrated for 2 h, then cooled to below 50°C, added with tackifier, evacuated to below -0.09 MPa, and continued to stir at 100 rpm for 40 min to obtain component A.
[0169] Component B:
[0170] First, the filler and white carbon black were dried and dehydrated in a drying room at 100°C for 48 hours for use;
[0171] The liquid polybutadiene polyol was vacuumed to -0.09 MPa at 120°C and dehydrated for 2 hours for later use;
[0172] Heat the asphalt and plasticizer to 120°C under stirring at 500 rpm, evacuate to -0.09 MPa and dehydrate for 2 hours to fully disperse the asphalt in the plasticizer, and set aside;
[0173] Then, isocyanate and liquid polybutadiene polyol were stirred at 100 rpm at 80°C and vacuumed to -0.09 MPa for reaction for 2 hours, followed by adding pre-dried fillers and white carbon black, pre-dehydrated and dispersed plasticizers and asphalt, antioxidants and water absorbents, stirring at 200 rpm at room temperature and vacuumed to -0.09 MPa for reaction for 1 hour to obtain component B.
[0174] Finally, the above-mentioned component A and component B are evenly mixed in a volume ratio of 1:1 to obtain a two-component polyurethane water-blocking adhesive.
[0175] The various properties of the two-component polyurethane water-blocking adhesive provided in each embodiment and comparative example were tested, and the testing method is as follows:
[0176] Hardness: GB / T 531.1-2008, Standard for the test method of indentation hardness of vulcanized rubber or thermoplastic rubber;
[0177] Water vapor transmission rate: GB / T 26253-2010, Determination of vapor transmission rate of plastic film and sheeting-Infrared detector method;
[0178] Shear strength: GB / T 7124-2008, Determination of tensile shear strength of adhesives (rigid material to rigid material);
[0179] Body strength: GB / T 528-2009, Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber;
[0180] Elongation at break: GB / T 528-2009, Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber;
[0181] PCT aging (120℃ / 100% RH / 0.2MPa): IEC60068-2-66, Environmental testing-Part 2: Test methods-Test Cx: Damp heat, steady state (unsaturatedpressurized vapor);
[0182] Ultraviolet radiation aging: GB / T 31881-2015, Test method for accelerated ultraviolet aging of automotive non-metallic parts and materials.
[0183] The test results are shown in Table 2 below.
[0184] Table 2
[0185]
[0186] The experimental results show that the two-component polyurethane water-blocking adhesive provided by the present invention can reduce the water vapor permeability of the system by adding liquid polybutadiene polyol to the system, and by adding antioxidants, the resistance of the glue to ultraviolet radiation can be improved; more importantly, the addition of asphalt has a positive effect on the system. With the increase in the amount of asphalt added, the water vapor permeability of the system gradually decreases, the flexibility is improved, and the PCT / ultraviolet radiation aging effect is improved. However, it is worth noting that excessive asphalt addition will reduce the hardness and bonding strength of the system. From the test results, adding 20wt% is optimal, and the shear strength of the system will be low when further increased to 30wt%. The experimental results of the comparative example show that when no asphalt is added, the ultraviolet radiation resistance of the system is significantly attenuated.
[0187] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A polyurethane water-blocking adhesive for a photovoltaic module frame, comprising a component A and a component B in a volume ratio of (0.8-1.2):1; The A component comprises: 5 to 10 parts by weight of modified castor oil polyol; 10 to 20 parts by weight of polyester polyol; 5 to 20 parts by weight of liquid polybutadiene polyol; 1 to 3 parts by weight of chain extender; 5 to 15 parts by weight of plasticizer; 20 to 40 parts by weight of asphalt; 20 to 40 parts by weight of filler; 1 to 3 parts by weight of white carbon black; 0.2 to 2 parts by weight of tackifier; The B component includes: 15 to 40 parts by weight of isocyanate; 10 to 40 parts by weight of liquid polybutadiene polyol; 10 to 20 parts by weight of plasticizer; 10 to 30 parts by weight of asphalt; 20 to 40 parts by weight of filler; 1 to 3 parts by weight of white carbon black; 0.2 to 2 parts by weight of antioxidant; 0.2 to 2 parts by weight of water absorbent.
2. The polyurethane water-blocking adhesive for photovoltaic module frames according to claim 1, characterized in that: The modified castor oil polyol is selected from Itoh Oil URIC AC-009 and / or Itoh Oil URIC AC-006; The polyester polyol is selected from Oleon RADIA 7285 and / or Oleon RADIA 7287; The liquid polybutadiene polyol is selected from Evonik Polyvest HT and / or Cray Valley Poly bdR45V.
3. The polyurethane water-blocking adhesive for photovoltaic module frames according to claim 1, characterized in that: The chain extender is selected from 2-ethyl-1,3-hexanediol and / or 2-butyl-2-ethyl-1,3-propanediol.
4. The polyurethane water-blocking adhesive for photovoltaic module frames according to claim 1, characterized in that: The plasticizer is selected from Rutgers Ruetasolv DI and / or Rutgers Novares L100; The tackifier is selected from BYK BYK-4511 and / or ShinEtsu KR-517.
5. The polyurethane water-blocking adhesive for photovoltaic module frames according to claim 1, characterized in that: The bitumen is selected from TOTAL AZALT 160 / 220 and / or Nynas Nybit E190.
6. The polyurethane water-blocking adhesive for photovoltaic module frames according to claim 1, characterized in that: The isocyanate is selected from carbodiimide-uretonimine modified 4,4'-diphenylmethane diisocyanate and / or 4,4'-dicyclohexylmethane diisocyanate.
7. The polyurethane water-blocking adhesive for photovoltaic module frames according to claim 1, characterized in that: The antioxidant is selected from one or more of BASF Irganox 1010, BASF Irgafos 168, and BASF Irganox B215.
8. A method for preparing the polyurethane water-blocking adhesive for a photovoltaic module frame according to any one of claims 1 to 7, comprising the following steps: a) Heat modified castor oil polyol, polyester polyol, liquid polybutadiene polyol, chain extender, plasticizer, asphalt, filler and white carbon black to 110°C to 130°C, mix and dehydrate under vacuum, then cool to below 50°C, add tackifier and mix under vacuum to obtain component A; b) After the isocyanate and liquid polybutadiene polyol are reacted for the first time, the dried filler, white carbon black, the dehydrated and dispersed plasticizer, asphalt, antioxidant and water absorbent are added to carry out a second reaction to obtain component B; c) Mixing the above component A and component B in a volume ratio of (0.8-1.2):1 to obtain a polyurethane water-blocking adhesive for a photovoltaic module frame; There is no order restriction for step a) and step b).
9. The preparation method according to claim 8, characterized in that: The mixing method of heating to 110° C. to 130° C. in step a) is stirring, and the stirring speed is 400 rpm to 600 rpm; The vacuum degree of the vacuum dehydration is -0.08MPa~-0.1MPa, and the time is 1.5h~2.5h; The vacuum degree of the vacuum mixing is -0.08MPa~-0.1MPa, the rotation speed is 50rpm~150rpm, and the time is 30min~60min.
10. The preparation method according to claim 8, characterized in that: The temperature of the first reaction in step b) is 70°C to 90°C, the rotation speed is 80rpm to 120rpm, the vacuum degree is -0.08MPa to -0.1MPa, and the time is 1.5h to 2.5h; The temperature of the second reaction is 10°C to 40°C, the rotation speed is 180rpm to 220rpm, the vacuum degree is -0.08MPa to -0.1MPa, and the time is 0.5h to 1.5h.
Citation Information
Patent Citations
Asphalt-based reactive polyurethane coating, as well as preparation method and application thereof
CN102604520A
Acid-resistant heatproof elastic bonding agent and preparation method thereof
CN105820790A
Two-component normal temperature non-curing asphalt polyurethane waterproof coating and preparation method thereof
CN110527424A
High-temperature-resistant two-component polyurethane structural adhesive for power battery and preparation method thereof
CN116574478A
Polyurethane resin composition
JP2019183125A
Cited By
Two-component polyurethane photovoltaic sealing water-blocking glue and preparation method thereof
CN122012008A
